Designing Interactive Illustrated Fable Storybook About Anger Management for Children Aged 6-8 Years - Faye Alicia; Ellis Melini; Brian Alvin Hananto; Eston Kamelang Mauleti (Jurnal Desain Komunikasi Visual Nirmana, 2026)
Childhood is an important period where parents have the opportunity to teach many things, one of which is anger management for the development of a child's emotional intelligence. However, the limited media available for parents to teach this independently at home presents its own challenges. In child counseling practice, counselors use various non-digital physical tools to maximize children's sensory involvement through images, colors, and interactivity. This approach can also be applied to a more familiar medium, such as an interactive fable illustration storybook equipped with parental guidance. The design process was carried out using the Design Thinking method and involved collaboration with a child counselor to ensure the project’s relevance and effectiveness. Prototype testing with the target audience showed that children gained a better understanding of how to manage and express anger, while parents found the book relevant and useful as a tool to open discussions with their children. This project demonstrates that the topic of anger management can be introduced in an enjoyable way through interactive visual media that supports involvement from both children and parents.